Increasing the Potential of Gerbo Village Through Community-Based Ecotourism Development on Mount Tumpeng: Peningkatan Potensi Desa Gerbo Melalui Pengembangan Ekowisata Berbasis Masyarakat Di Gunung Tumpeng - Shobich, Achmad; Suprianto, Suprianto (Proceedings of The ICECRS, 2025)
General Background: Ecotourism is increasingly recognized as a sustainable approach to tourism that balances environmental conservation with community empowerment. Specific Background: Gunung Tumpeng in Desa Gerbo, Pasuruan, possesses significant ecotourism potential due to its natural beauty and cultural richness. Knowledge Gap: However, limited research has explored how local initiatives and stakeholder collaboration can effectively address the persistent challenges in underdeveloped ecotourism sites. Aims: This study aims to examine the development of ecotourism in Gunung Tumpeng by identifying its potentials, existing challenges, and the contributions of local programs, particularly the KKN-P 31 UMSIDA initiative. Results: Using observation, interviews, and direct community involvement, the study found that despite the area’s natural appeal, critical issues such as inadequate infrastructure, insufficient promotional efforts, and weak community-based management hinder its growth. Novelty: The installation of directional plaques by KKN-P 31 UMSIDA represents a practical and context-sensitive intervention to improve visitor safety and experience, demonstrating a replicable model of university-community collaboration. Implications: These findings underscore the necessity for multi-stakeholder engagement and strategic planning in ecotourism development, offering insights for policymakers, academic institutions, and local communities aiming to enhance the sustainability and appeal of emerging tourist destinations. Keywords: Ecotourism, Gunung Tumpeng, Community Empowerment, Infrastructure, Stakeholder Collaboration Highlights: Local initiatives like KKN-P 31 UMSIDA play a key role in safety improvements. Stakeholder collaboration is vital to overcome development barriers. Sustainable planning is needed to maximize ecotourism potential.